Keperluan Penubuhan Unit Bimbingan dan Kaunseling Bagi Pelatih-pelatih Pegawai Kawalan Trafik Udara di Kolej Penerbangan Awam di Malaysia - Mohd. Salihin, Yahya (2004)
This study was conducted to study the need of setting up a counseling and guidance unit for trainees of the Air Traffic Control Officers at the Civil Aviation College Malaysia. This unit is required to assist the trainees confront and overcome problems that may affect their performance which in turn, impact the Civil Aviation College Malaysia in a negative manner. Questionnaires were used as the research instrument. 29 respondents for this study are trainees of the Air Traffic Control Officers attached to the Civil Aviation College Malaysia who participated by answering the questionnaires provided. Sampling was not used due to the small respondents. The questionnaires were designed based on the objectives of the research. It was divided into three sections, A,B and C with a total of 43 questions. The consistency reliability of the research instrument was checked through a pilot test done on the Air Traffic Controllers from Subang Air Traffic Control Centre. The Cronbach Alpha coefficient test was done for thie questions constructed and the Alpha Score obtained was 0.7708. The analysis of the data was carried by using the SPSS for Windows Ver.11. Descriptive such as percentage, mean and median scores showed 86.2 percent agree to the need of the counseling and guidance unit. The study showed that there is a requirement for the trainees of the Air Traffic Control Officers to have the counseling and guidance unit in reducing problems faced while undergoing training. Few recommendations were made to how this unit can be used for the development of human resources. The need to study the counseling and guidance unit should be extended to the Air Traffic Control Officers serving in the Air Traffic Control Centre since the stress level is much greater there.